Identification and characteristics of distressed patients with coronary heart disease and insufficiently controlled medical risk factors: baseline findings and sex differences from the multicenter TEACH trial - Herrmann-Lingen, Christoph; Sadlonova, Monika; Becker, Ingrid; Bersch, Kristina; Geiser, Franziska; Hellmich, Martin; Kindermann, Ingrid; Michal, Matthias; Nöhre, Mariel; Petersmann, Astrid; Wachter, Rolf; Belnap, Birgit Herbeck; et al. (Frontiers in Psychiatry, 2025)
IntroductionMedical risk factors and psychological distress are important targets for secondary prevention of coronary heart disease (CHD). The multicenter randomized controlled TEACH study is the first trial testing a blended collaborative care (BCC) intervention vs. usual care in a cohort of only patients with CHD. The current manuscript analyzes the availability of distressed CHD patients for a BCC intervention trial and the baseline risk profile of the randomized cohort, especially focusing on sex differences.MethodsHospitalized CHD patients with positive HADS and/or PSS-4 screening were rescreened three months later and those still distressed were offered participation in the RCT if they had insufficiently controlled medical risk factors (smoking, physical inactivity, elevated blood pressure, LDL cholesterol, and/or HbA1c). The current manuscript describes the TEACH screening process and presents baseline data of the randomized cohort.ResultsOf 2,785 screened patients, 457 patients with persistent distress and insufficiently controlled risk factors were randomized. Older age and lower distress but not sex independently predicted dropout before randomization. In the randomized cohort (mean age 62.9 ± 9.5 years, 77.4% men), women were older than men (p=0.025), more likely to be retired (52.4% vs. 38.6%; p=0.012) and to live without a partner (48.6% vs. 24.8%, p<0.001). Compared to men, they had lower diastolic blood pressure (p=0.003) but higher rates of physical inactivity (56.0% vs. 41.8%; p=0.012) and positive family history of premature atherosclerotic disease (45.7% vs. 29.8%; p=0.009). They also had a lower rate of previous coronary bypass surgery (21.0% vs. 39.2%, p<0.001). A mental disorder had been diagnosed in 54% of all randomized patients and 42% had previously received mental health treatment, both reported substantially more frequently by women than men (both p<0.001). Satisfaction with care before the trial did not differ by sex but was far lower for psychosocial care than for treatment of heart disease (p<0.001).DiscussionTEACH enrolled a patient sample with persisting distress and a typical risk factor profile. Women differed from men in relevant aspects of their RF profiles and mental health and should receive special attention in future analyses and treatment planning for patients with CHD.Clinical Trial RegistrationGerman Clinical Trials Register, https://drks.de/search/de/trial/DRKS00020824, identifier DRKS00020824.